2017
DOI: 10.1002/fsn3.477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two sources of iodine delivery on breast milk iodine and maternal and infant urinary iodine concentrations in southern Ethiopia: A randomized trial

Abstract: Iodine deficiency during pregnancy and lactation could expose the infant to severe iodine deficiency disorders. A randomized supplementation trial among rural lactating women was conducted in Sidama zone, southern Ethiopia, to compare the methods of iodine delivery on breast milk iodine, and on maternal and infant urinary iodine concentrations. Women were randomly assigned either to receive 225 μg iodine as potassium iodide capsule daily for 6 months or 450 g of appropriately iodized salt (30–40 μg I as KIO3/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…A strength of this approach is that the sample collection method is easy, painless, and non‐invasive, very important characteristics for use in paediatric settings. We found urine collection into a nappy with cotton wool balls to be acceptable to parents and efficient, as has been described by others (Ahmad et al, ; Gebreegziabher & Stoecker, ). This method of sample collection would work for clinical and research purposes if a successful assay system to differentiate breastfeeding from formula feeding was established.…”
Section: Discussionsupporting
confidence: 79%
“…A strength of this approach is that the sample collection method is easy, painless, and non‐invasive, very important characteristics for use in paediatric settings. We found urine collection into a nappy with cotton wool balls to be acceptable to parents and efficient, as has been described by others (Ahmad et al, ; Gebreegziabher & Stoecker, ). This method of sample collection would work for clinical and research purposes if a successful assay system to differentiate breastfeeding from formula feeding was established.…”
Section: Discussionsupporting
confidence: 79%
“…The current study was conducted in 2013, following the rapid implementation of a salt iodization program in 2012. Presumably as the result of the program implementation, our study population showed higher UIC and BMIC than previous studies [12].…”
Section: Discussionmentioning
confidence: 54%
“…A larger relative decline of thyroid volume was observed in the younger compared to older females from a site where iodine deficiency was moderate [11]. In our study, women supplemented with adequately iodized salt had breast milk iodine concentrations that were not different from women who received a daily capsule containing 225 ug iodine; infant urinary iodine concentrations also were not significantly different based on source of maternal iodine supplement [12].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations